KERUKUNAN HIDUP ANTAR UMAT BERAGAMA BERBASIS KEARIFAN LOKAL DI KAMPUNG LOLOAN, JEMBRANA, BALI - Sabarudin Sabarudin; Mahmud Arif (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
Diversity is the reality of Indonesian life, whether ethnically, linguistically, culturally, or religiously. In that context, examining the diversity of Balinese society is certainly very interesting considering it is not just a